Smart Metering Technologies - Kaur, Inderpreet (IntechOpen, 2021)
This book discusses the use of smart metering technology (SMT) in diverse areas including electrical power grids, communications, transportation, and more. Chapters cover such topics as smart meters, off-grid electrification, standardized risk management procedures for mini-grids, and SMT in academics, among others.